The semicontinuous frame quasi-uniformity, revisited - Ferreira, Maria João (2009)
In this note we present a new treatment of the pointfree version of the semicontinuous quasi-uniformity based on the new tool of the ring of arbitrary (not necessarily continuous) real-valued functions made available recently by J. Guti errez Garc a, T. Kubiak and J. Picado [Localic real functions: a general setting, Journal of Pure and Applied Algebra 213 (2009) 1064-1074]. The purpose is to show how the basic facts about the semicontinuous quasi-uniformity can be easily presented and proved with that tool at hand.